BUSSINESS PROCESS REENGINEERING APPROACH FOR QUALITY REPORTING PROCESS (Case Study at PT D. Perdana, Pasuruan) - Oktavianty, Oke (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2018)
Business Process Reengineering (BPR) is an effective and popular approach to deal with global competitiveness. It can be applied by companies to improve the effectiveness and efficiency of existing business processes. Developing a continual improvement and abandon the conventional ways will increase the work efficiency. The process can be transformed to create a more efficient process with value-added and get more benefit to the company in the future. In this study, the evaluation of quality reporting process was conducted by BPR approach. The re-design and reconstruction of the process with information technology implementation give a significant improvement in the work efficiency, both efficiency value, step number, and time efficiency.